Tailored susceptibility-guided therapy via gastric juice PCR for the first-line H. pylori eradication, a randomized controlled trial - Meng-Shu Hsieh; Fu-Chen Kuo; Meng-Chieh Wu; Jiunn-Wei Wang; Chung-Jung Liu; Neng-Sheng Chu; Pei-Yun Tsai; Ping-I Hsu; I-Chen Wu; Jeng-Yih Wu; Deng-Chyang Wu; Fang-Jung Yu; et al. (Journal of the Formosan Medical Association, 2022)
Background/Purpose: Clarithromycin-based standard triple therapy is still commonly adopted by 81.4% of physicians in real-world practice but yields low eradication rates. Therefore, we conducted this study to compare the efficacy of gastric juice-guided therapy for first-line eradication with the standard triple therapy, in order to provide an alternative to real-world practice. Methods: A total of 182 treatment-naïve Hp-infected patients were included and randomly allocated to either susceptibility-guided therapy (SGT) with gastric juice PCR or Clarithromycin-based standard triple therapy (STT) for 7 days. Results: The intention-to-treat eradication rates were 89% (81/91) in SGT and 75.8% in STT (p < 0.031). The per-protocol eradication rates were 91.0% (81/89) in SGT and 79.3% (69/87) in STT (p < 0.034). Among the subgroups of different antibiotic resistance, patients with SGT demonstrated superior eradication rates (91.7% vs 45.5%, p < 0.027) in the subgroup of both clarithromycin resistance and levofloxacin resistance. Conclusion: This prospective randomized controlled trial demonstrated the reliable efficacy of susceptibility-guided therapy via gastric juice PCR for the first-line Hp eradication. In Asia-Pacific area, where standard triple therapy is still adopted by the majority of the physicians, it is a recommended alternative to overcome the increasing antibiotic resistance.